FINANCIAL POTENTIAL FOR EXPANDING THE OPPORTUNITIES OF A SMALL ENTERPRISE UNDER THE CONDITIONS OF SUSTAINABLE DEVELOPMENT - Віталій Ніценко; Алла Іващенко; Віталій Радько; Валентина Середа; Олена Кузьменко; Іван Дімов (Фінансово-кредитна діяльність: проблеми теорії та практики)
This study focuses on the development of a macroeconomic model for assessing the financial potential of small enterprises, in particular in the context of their impact on value added. Most enterprises need financing for their current operations, acquisition of fixed assets and implementation of growth strategies. However, the existing assessment methods in the scientific literature are limited in their comprehensive reflection of the impact of entropy. In our study, we applied linear multivariate regression, which made it possible to describe the impact of financial capacity on small business development, in particular, in terms of added value. The results of the study are particularly relevant for small businesses in countries such as Austria, Belgium, Croatia, Germany, France, Italy, Spain, Poland, Portugal, and Slovakia, where the model demonstrates efficiency. We have noted that in Ukraine, on the contrary, efficiency is modelled primarily due to the weaker correlation of indicators. That is why additional factors, including non-economic factors from the informal sector (e.g., shadow financial flows, information asymmetry, poor infrastructure, corruption, etc.), were extremely helpful in assessing the financial potential and impact on small businesses in Ukraine.